Modification Design and Test of Heavy Load Gear of Reducer for Mine based on MASTA - Wei Bingyang; Li Yu; Ouyang Hongfei; Chen Aiming (Jixie chuandong)
Taking the last gears of the mine reducer named JS75 as the research object,by using the gear microscopic modification module of MASTA,the comparison and analysis of the contact spots,transmission error and harmonic amplitude before and after modifying are carried out. The determination of optimum modification method and amount is completed. The test of vibration and noise and spectrum analysis are carried out on the reducer under no- load and load by using M + P testing system. It is proved that the modification of the heavy load gears in last stage is very effective to control the vibration and noise of the transmission system,and the high speed spiral bevel gears has a very important influence on the dynamic performance of the reducer.